Combustion and emission performance analyzes on the blend of waste cooking oil / Azadirachta indica oil biodiesel / carbon nano tubes in diesel engines - T. Sathish (International Journal of Thermofluids)
Fossil fuels are the main energy source, and as a result of their use, we are producing more emissions into the atmosphere (Air Pollution). The researchers explored a range of oxygenated fuels to find a substitute for cutting down on fossil fuel energy consumption and lowering emissions. This study also extends such search by carrying out the transesterification process to produce sustainable biodiesel from waste cooking oil (WCO) and Azadirachta indica oil as an alternate fuel for diesel engines. Furthermore, we use carbon nanotube nanoparticles as additives at a ratio of approximately 50 ppm and 100 ppm to enhance the engine performance closer to or even better than traditional diesel in terms of combustion efficiency, brake thermal efficiency and reduced emissions. We conducted the experiments in a diesel engine test rig at a constant speed of 1500 rpm with varying loads of No load, 25 %, 50 %, 75 %, and 100 % and using four blends other than pure diesel (D) such as Azadirachta indica biodiesel 25 % and WCO 75 % (NB25WCOB75), Azadirachta indica biodiesel 50 % and WCO 50 % (NB50WCOB50), Azadirachta indica biodiesel 75 % and WCO 25 % (NB75WCOB25), NB25WCOB75 and CNT at 50ppm (NB25WCOB75CNT50PPM), and NB25WCOB75 with CNT at 100ppm (NB25WCOB75CNT100PPM). The observed BTE and BSFC results of about 31 % and 0.32 g/kWh using the NB50WCOB50CNT50PPM fuel blend. Similarly, the recorded values for CO, UHC, NOX, and smoke were approximately 4 g/kWh, 0.12 g/kWh, 12.05 g/kWh, and 24 %. This result demonstrates that the NB50WCOB50CNT50PPM blend fuel offers superior fuel properties and lower emission characteristics when compared to other fuel blends.